2020
DOI: 10.1007/s10103-020-03142-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-excisional laser therapies for hemorrhoidal disease: a systematic review of the literature

Abstract: Non-excisional laser therapies are emerging treatment for grades II and III hemorrhoidal disease (HD). However, so far, their efficiency is based on low-level evidence. Therefore, we aimed to systematically review the efficiency of non-excisional laser therapies for HD. MEDLINE/Pubmed, Web of science, Embase, and Cochrane were searched from database implementation until the April 17th, 2020. We included studies reporting at least one of surgical indicators of postoperative outcomes of laser therapies, encompas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The application of laser in proctology was first described by Karahaliloglu in 2007, who reported the first results of nonexcisional therapy of hemorrhoidal disease (HD) called laser hemorrhoidoplasty (LHP). Since then, many relevant studies, including randomized controlled trials, demonstrated that LHP is safe and effective for the treatment of HD while it provides a very low pain and discomfort period [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The application of laser in proctology was first described by Karahaliloglu in 2007, who reported the first results of nonexcisional therapy of hemorrhoidal disease (HD) called laser hemorrhoidoplasty (LHP). Since then, many relevant studies, including randomized controlled trials, demonstrated that LHP is safe and effective for the treatment of HD while it provides a very low pain and discomfort period [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the three RCTs had a significantly shorter operation time with LH versus open HC (mean 33.1 min ± 7.3 vs. mean 52.6 min ± 15.6, p < 0.001; mean 30.6 min ± 4.9 vs. mean 50.5 min ± 12.1, p < 0.001; mean 15 min±5.6 vs. mean 29 min±10.3, p < 0.001, respectively). Four studies described the hospitalization duration, which ranged from 3 to 48 h and was similar to open HC [19].…”
Section: Resultsmentioning
confidence: 99%
“…These reported approximations do not include haemorrhoid sufferers who evade medical help and rely on over-the-counter medications [ 2 , 3 ]. Non-excisional hemorrhoidal procedures have been gaining popularity as a treatment for these symptomatic haemorrhoids as these procedures are significantly less painful as minimally invasive procedure [ 4 6 ]. Furthermore, post-operative complications and recurrence rates are comparatively low for non-excisional procedures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Laser Hemorrhoidoplasty (LHP) utilizes diode lasers, in a non-excisional manner, and is associated with reduced post-operative pain. It is particularly useful for grade 1–2 haemorrhoids, where prolapse is less significant [ 6 , 9 ]. However, a relatively common complication is post-operative bleeding, with Clavien-Dindo Class III bleeding in the region of 1–5% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%